Efficacy of Back Bracing in Treating Chronic Low Back Pain - John S. Vick; Jessica Zimmerman; Stephanie Hicks; Abigail Biekert; Alaa Abd-Elsayed (Brain Sciences)
Chronic low back pain (CLBP) negatively impacts quality of life and contributes to a significant economic burden. One conservative management strategy for CLBP is lumbar back bracing. Despite the benefits of back bracing for improving pain and function, there remains hesitance to use the therapy long term due to unfounded fear related to muscle weakness, deconditioning, or joint contracture. Objective: The purpose of this study was to examine the outcomes for patients with CLBP who were managed with lumbar back bracing and physical therapy. Methods: This was a single-site, retrospective chart review. Results: Patients were included in the study if they were treated for CLBP with back bracing for at least one hour daily and physical therapy for twelve weeks. Pain was assessed at three, six, and twelve months using the 11-point Visual Analogue Scale (VAS). Function was assessed at three months using the Oswestry Disability Index (ODI). The VAS score reduced from 6.28 +/− 2.32 to 3.96 +/− 2.66 at three months (p < 0.001) for 198 patients. At six and twelve months, the VAS score reduced to 3.74 +/− 2.73 (p < 0.001) and 3.23 +/− 2.29 (p < 0.001), respectively. The total ODI score for 199 patients improved from 46.56 +/− 15.30 to 33.13 +/− 19.99 (p < 0.001) at three months. Conclusion: Back bracing in combination with physical therapy is effective for treating low back pain.